Peruvian economists: training and professional performance - Bendezú Jiménez , Héctor Javier; Burgos Zavaleta , Fernando; Gutierrez Alvarado, Tiffany (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
Over time, economists have taken on challenge after challenge; however, they have not been indifferent to the new demands of society over time. The purpose of this study is to know the perspectives, assessments and interests of employers and groups regarding the professional and work performance of Peruvian economists. A qualitative study was carried out through surveys applied to 15 companies of economists from the Universidad Nacional Mayor de San Marcos. The results show that users are looking for professionals with a training that adapts to the permanent change in society, specialization and the use of new technological tools for their professional development, without losing the essence of what it is to be an economist. This study concludes that employers value more that economists have knowledge of technology and mastery of their specialty, and that in light of these results, the improvement of specialization courses in the curricula should be taken into account, especially a improvement in soft skills and use of technology.